IMPOLITENESS STRATEGIES USED BY CUSTOMERS OF MUARA BUNGO HOME CREDIT - Santy, Gressilia Pedra; Afrilesa, Rini; Magria, Vera (Krinok:Jurnal Linguistik Budaya, 2023)
This research analyzes the impoliteness strategies used by customers of Muara Bungo Home Credit through WhatsApp text messages and how the strategies function in delivering the impoliteness between the customers and the employees of Home Credit. The purposes of this research are (1) to identify the types of impoliteness strategies used by customers of Muara Bungo Home Credit; (2) to analyze the functions of impoliteness strategies aimed by customers of Muara Bungo Home Credit.. The research also applied descriptive qualitative method, with the customers’ WhatsApp text messages as the source of the data.The result of this research shows that, (1) there are 19 data of impoliteness strategies found in the WhatsApp text messages from customers’ of Muara Bungo Home Credit, which are sarcasm/mock politeness (4 data), positive impoliteness (3 data), negative impoliteness (6 data) and bald on record impoliteness (6 data) which occurred the most in the research; (2) all 19 data of impoliteness strategies used by the customers had different functions, which are affective (7 data), entertaining (4 data) and coercive (8 data), which is the most applied function in the research.